Finite Difference Method for Solving Fractional Hyperbolic Partial Differential Equations - Mohammed, G. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, the finite difference method is used to solve fractional hyperbolic partial differential equations, by modifying the associated explicit and implicit difference methods used to solve fractional  partial differential equation. A comparison with the exact solution is presented and the results are given in tabulated form in order to give a good comparison with the exact solution